The importance of information, motivation, and behavioral skills (IMB): Healthcare provider perspectives on improving adherence to cervical cancer screening among at-risk women - Anjanette Wells; Vanessa Allen-Brown; Nadia Alam; Caroline Skulski; Amanda L. Jackson; Thomas J. Herzog (Elsevier, 2021)
Objective: To understand the theoretical framework of how information, motivation, and behavioral skills (IMB) independently and collectively affect cervical cancer screening and testing adherence. Study design: Qualitative study. Methods: Data collected from three focus groups and seven individual interviews, with 33 healthcare providers, ranging from community health navigators, Ob-Gyn MD's, nurses, care coordinators, medical assistants, and outpatient managers, representing a grassroots community health agency, a large cancer center, and a public sector health clinic. We recruited providers over a five-month period in the summer to fall of 2019. Provider interviews and focus groups were structured with four to eleven participants per group and were audio-recorded. This study was rooted in grounded theory, analyzing data using the iterative process of Coding, Consensus, Co-occurrence, and Comparison to identify common themes. Results: Emerging qualitative findings include the relevance of information, the interaction between information and motivation, the role of behavioral skills, and the symbiotic relationship between information, motivation, and behavioral skills (IMB). Most notable is this interdependency between IMB components, with the core of this relationship being the critical link of coordinating adherence. Conclusion: This knowledge will help advance and expand IMB intervention components to improve time to cervical cancer screening and follow-up adherence among at-risk communities. Particularly given COVID-19 barriers, which disproportionately affect at-risk women, this study has practice implications that inform the development of cervical cancer screening practice interventions and strategies to improve adherence, while ensuring safety for both patients and providers.